Joint Position Statement on Degree Requirements for Paramedics. (4th May 2019) - Caffrey, Sean M.; Barnes, Leaugeay C.; Olvera, David J.
Abstract: The National Association of EMS Educators, the National EMS Management Association, and the International Association of Flight and Critical Care Paramedics believe the time has come for paramedics to be trained through a formal education process that culminates with an associate degree. Once implemented a degree requirement will improve the care delivered by paramedics and enhance paramedicine as a heath profession.